ANALYSIS OF THE ECONOMIC EFFICIENCY AND SOCIAL IMPACT OF ECOLOGICAL MARKETING STRATEGIES IN THE FIELD OF CLEANING PRODUCTS - Baqoyeva Dilfuza Maqsud qizi (American Journals, 2025)
This study explores the economic effectiveness and social impact of ecological marketing strategies in the hygiene products sector. The analysis reveals that green approaches help reduce costs, enhance consumer trust, and strengthen brand loyalty. Eco-labeling, sustainable packaging, innovation, and transparent communication emerged as the most effective strategies. The findings confirm that ecological marketing can serve as a practical and impactful management tool.
Keywords: Ecological marketing, hygiene products, economic effectiveness, social impact, green strategy, brand loyalty